TWEAK Receptor Deficiency Has Opposite Effects on Female and Male Mice Subjected to Neonatal Hypoxia–Ischemia - Kichev, Anton; Baburamani, Ana A.; Vontell, Regina; Gressens, Pierre; Burkly, Linda; Thornton, Claire; Hagberg, Henrik (Frontiers in Neurology, 2018)
Tumour necrosis factor (TNF)-like weak inducer of apoptosis (TWEAK) is a multifunctional cytokine member of the TNF family. TWEAK binds to its only known receptor, Fn14, enabling it to activate downstream signalling processes in response to tissue injury. The aim of this study was to investigate the role of TWEAK signalling in neonatal hypoxia-ischemia (HI). We found that after neonatal HI, both TWEAK and Fn14 expression were increased to a greater extent in male compared with female mice. To assess the role of TWEAK signalling after HI, the size of the injury was measured in neonatal mice genetically deficient in Fn14 and compared with their wild type and heterozygote littermates. A significant sex difference in the Fn14 KO animals was observed. Fn14 gene knockout was beneficial in females; conversely, reducing Fn14 expression exacerbated the brain injury in male mice. Our findings indicate that the TWEAK/Fn14 pathway is critical for development of hypoxic-ischemic brain injury in immature animals. However, as the responses are different in males and females, clinical implementation depends on development of sex specific therapies.